Laboratory study on impulse current characteristics of clay. Issue 3 (June 2017) - Rao, Pingping; Chen, Qingsheng; Nimbalkar, Sanjay; Liu, Yang
Abstract : Lightning is recognised as one of the most detrimental natural disasters. While numerous research studies were carried out on the lightning impulse characteristics of the grounding system and the critical breakdown characteristics of soil, little attention was paid to the impulse current characteristics of soils when lightning strikes. In this study, the performance of typical soft soil in Shanghai under the action of lightning is analyzed. Different factors, including the impulse current waveforms, the front time and half peak time of impulse current, the quantity of electric charge and absorption of unit heat, have been studied by performing a series of laboratory tests. The test results show that the variation of impulse current due to lightning strike is time dependent. The higher the soil temperature, the larger the peak impulse current produced during lightning strike. The value of the front time decreases exponentially, while the value of the half peak time decreases linearly with the rise of soil temperature. Novel empirical relationships between the impulse current characteristics of soil and soil temperature are proposed, with the aim of providing useful practical references for the design of a grounding system for lightning strikes.